Fighting gender violence with behavioral public policy: scope and limitations - Alejandro Hortal (Retos: Revista de Ciencias de la Administración y Economía, 2023)
Since the concept of “nudge” was introduced in 2008 by Thaler and Sunstein, proposing that small interventions based on changes in choice architectures can alter people’s behavior and make it easier for them to achieve their desired goals, the application in public policy of behavioral economics has gained significant attention. This has led to the emergence of different types of policies based on behavioral insights, which have been used in a variety of areas, including health or finance, with the goal of promoting well-being and addressing social and economic issues. After providing a basic theoretical background as a frame of reference to understand gender violence, this study explores the use of tools from the field of behavioral economics as it is applied in public policy. Regulatory (paternalistic) and non-regulatory (libertarian) interventions based on behavioral insights will be considered: nudges, boosts, shoves, budges, or sludge audits, are examined as potential interventions to use in matters related to this type of violence. After evaluating these behavioral policy instruments and their potential effectiveness, the limitations of the behavioral perspective are recognized, and the need for a multifaceted approach to combating gender violence is acknowledged. The article concludes by arguing that public policies addressing gender violence should not only utilize behavioral tools but should also incorporate strategies related to education, legislation, and social norms.